2016
DOI: 10.1016/j.bbi.2016.04.015
|View full text |Cite
|
Sign up to set email alerts
|

Neurons and astroglia govern microglial endotoxin tolerance through macrophage colony-stimulating factor receptor-mediated ERK1/2 signals

Abstract: Endotoxin tolerance (ET) is a reduced responsiveness of innate immune cells like macrophages/monocytes to an endotoxin challenge following a previous encounter with the endotoxin. Although ET in peripheral systems has been well studied, little is known about ET in the brain. The present study showed that brain immune cells, microglia, being different from peripheral macrophages, displayed non-cell autonomous mechanisms in ET formation. Specifically, neurons and astroglia were indispensable for microglial ET. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 55 publications
3
27
0
2
Order By: Relevance
“…Previous studies showed that microglial activation and proliferation are regulated by CSF‐1 (Chu et al . ; Guan et al . ; Okubo et al .…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies showed that microglial activation and proliferation are regulated by CSF‐1 (Chu et al . ; Guan et al . ; Okubo et al .…”
Section: Resultsmentioning
confidence: 99%
“…Upon activation, CSF1R associates with several signaling molecules, notably phosphoinositide 3-kinase (PI3K) [58]. CSF1R also activates Akt [11], and it induces ERK1/2-mediated signaling in microglia [9]. Akt [22,67] and ERK1/2 [19] are involved in the phagocytic process.…”
Section: Discussionmentioning
confidence: 99%
“…6,9,46 Fewer reports exist in relation to the central mechanisms of endotoxin tolerance, even though this topic has been aptly addressed in important recent studies in the literature. 47,48 Besides, in an elegant experiment described by Chu et al 49 while neurons and astroglia are affected by chronic neuroinflammation, microglia fails to develop endotoxin tolerance. The authors concluded that the absence of microglial endotoxin tolerance could be important for the pathogenetic mechanisms involved in inflammation-associated neuronal damage.…”
Section: Discussionmentioning
confidence: 99%